EFEKTIVITAS PELAYANAN PEMBAYARAN PAJAK KENDARAAN BERMOTOR DI KANTOR SAMSAT PEKANBARU SELATAN - Al Putri Abral; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is a result of research that describe the effectiveness of tax payment service of vehicle in south pekanbaru samsat office. In the implementation of vehicle tax payment service (PKB). Samsat is an abbreviation of "One Stop Administration System" consists of 3 institutions namely Regional Revenue, Police Service and Jasa Raharja Service. To find out how the effectiveness and the factors that affect the service of vehicle tax payment in the south pekanbaru samsat office will use the indicators by Sondang P. siagian’s theory. The indicators is time, accuracy and style of service provider.The purpose of this study to determine the effectiveness of vehicle tax payment service in the south Pekanbaru samsat office, in addition to know the factors that affect the effectiveness of tax payment service vehicles in the office of South Pekanbaru Samsat. In this study the authors use descriptive qualitative methods that provide a description of the situation and to analyze the data based on observations and interviews in the field.The result of the research on the effectiveness of the tax payment service of the vehicle in the south Pekanbaru samsat office is not yet effective and found the difference in the previous year 2016, in terms of time it could be said fast, but in terms of accuracy and service provider style has not changed from the previous year As there is no supervision on brokers and not all officers provide 3 s service that is smile, greeting, and polite. In addition, the factors that affect the service tax payment vehicles in southern Pekanbaru samsat is the leadership, system,, infrastructure, information and communication, supervision and community participationKeywords: Effectiveness, Public Service, Vehicle Tax, South Pekanbaru Samsat